Product Innovation and Its Impact on Total Sales of Manufacturing Firm in Indonesia: A Propensity Score Matching Analysis - Septyati, Widya; Rachmat Pambudi; Lukman M Baga; Khairunnisa Ramadini (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Objective – This research aims to analyze the impact of product innovation on total sales of manufacturing firm in Indonesia Design/methodology/approach – Using a quantitative approach, this research uses secondary data, namely survey data from 1.025 Indonesian manufacturing companies in 2015. The data analysis used in this research is Propensity Score Matching (PSM) Findings – The results of the study show that manufacturing companies that innovate products receive total sales 4.57% higher than the control group (companies that do not innovate products), ceteris paribus. From these results, it can be concluded that to improve the innovation performance of Indonesian manufacturing companies, company activities and government policies must be aimed at factors that can support the level of company innovation. Research limitations/implications – This study uses secondary data, namely survey data of 1025 Indonesian manufacturing companies in 2015 obtained from the World Bank. This survey was conducted on small, medium and large manufacturing companies located in the provinces of West Java, East Java, Central Java, DKI Jakarta, Banten, South Sulawesi, North Sumatra, Bali and Lampung. As a recommendation, the author suggests further research in a different kinds of companies in Indonesia. Practical implications – This study will encourage companies to do more innovation in their business as the innovation has a positive relation with total sales. Originality/value – Currently there is no research that analyzes how and how much impact the innovation has on the company's total sales, especially in Indonesia. Therefore the originality lies in the whole research.